Molecular Weight Determinations Of Low Molecular Weight (LMW) Heparins By Ultracentrifugation And High Pressure Liquid Chromatography - Barlow, Grant; Sugisaka, N; Petracek, F J (Thrombosis and Haemostasis, 1981)
Molecular weights were independently determined on nitrous acid depolymerized LMW heparin fractions ranging from 2-15 daltons using the analytical ultracentrifuge and high pressure liquid chromatography (HPLC).Sedimentation-diffusion equilibria were obtained in the analytical ultracentrifuge using speeds ranging from 20,000 to 56,000 rpm. Near theta conditions were obtained using 0.5M NaCl as the solvent. Calculations of molecular weight distributions and, from those figures, weight average molecular weights were made using the method described by Scholte (N.Y. Acad Sci. 164, 156, 1969). The results show that weight average values as low as 2,000 daltons can be determined.Sedimentation-diffusion equilibria were obtained in the analytical ultracentrifuge using speeds ranging from 20,000 to 56,000 rpm. Near theta conditions were obtained using 0.5M NaCl as the solvent. Calculations of molecular weight distributions and, from those figures, weight average molecular weights were made using the method described by Scholte (N.Y. Acad Sci. 164, 156, 1969). The results show that weight average values as low as 2,000 daltons can be determined.The HPLC results were obtained using previously described methods (Fed Proc. 36, 89, 1977) and a new highly efficient gel column (TSK gels). Fractionated dextrans were used as reference standards.